Evaluasi Komposisi Proksimat Gandum Lokal Varietas Guri 5 Pasca Penyimpanan Jangka Panjang - Sarlina Palimbong; Djoko Murdono; Tinjung Prihtanti (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2026)
Whole wheat flour is generally made from fresh whole wheat grains to maintain its nutritional quality and functional properties. However, information on the nutritional composition of locally produced whole wheat flour stored for long periods (>24 months) remains very limited, especially in the context of simple storage systems commonly used at the farmer level. This study aims to evaluate the proximate composition of local whole wheat flour of the Guri 5 variety under two material conditions after 28 months of storage. Wheat grains were stored for 28 months at room temperature with a relative humidity of around 75% in two conditions, namely with spikelets (cleaner) and without spikelets (blower). The parameters analysed included moisture, ash, protein, starch, fat, and crude fibre content with three replications. Data were analysed using a one-way ANOVA at the 95% confidence level. The results showed that the treatment conditions produced significant differences (p<0.05) in the moisture, ash, starch, fat, protein, and crude fibre content of the flour. Flour from the blower treatment had a higher fat content (9.99%) than flour from the cleaner treatment (1.99%), suggesting the possible contribution of the fat-dense germ fraction to the final flour. In general, the results of this study indicate that although differences in the physical condition of the germ significantly affect the proximate composition of local whole wheat flour stored for 28 months, the final product still has great potential for use as a food ingredient. These findings provide initial insights into the nutritional profile of locally produced whole wheat flour after long-term storage under simple conditions.